Kolaż - rzeźbienie rzeczywistości - Karpowicz, Agnieszka (Wydawnictwo Naukowe UAM, 2007)
The birth of the technique of collage in the XXth century is the attempt to break through the borders between art and life. The art abandons fiction, for the first time annexing into its field waste and splinters of reality and next entering the real life. Anthropological understanding of artistic phenomena enables alternative to poststructuralist and postmodern view on the art of collage. It allows a constructive question to the phenomena to be posed and answered: what collage constructs, what it expresses and to what it reacts, whether it expresses the new consciousness? The slogan: "life itself is art and art is life" is the effect of collage, which participates in all genres and artistic forms that attempt to embrace non-artistic activities, melt into the sequence of events, act in the real space, conduct single actions, blowing over like events in the real life. Making art may be understood as the synonym for humanity. With the use the collage technique artists realize first of all that the artistic activity is part of reality and natural consequence of creative potential of humankind. Collage teaches how to locate pieces of art among other creative work. The collage technique shows that the Art is an everyday creation and output.
Collage Carving the Reality in the XXth Century Art